Knowledge, Attitudes, and Practice of Cosmetic Procedures among Population of Majmaah, Saudi Arabia, 2019-2020 - Abdulaziz M. Al Hindi, Sawsan M Abdalla, Batool A. Al-Mutairi, Farah A. Alnasser, Renad O. Alhegail, Raghad G. Al-Ghannam, Amirah F. Almutairi, Abdulmalik B Albaker (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Cosmetic procedures have been growing recently among men and women. Cosmetics procedures refer to both surgical and non-surgical procedures. For example, rhinoplasty (nose surgery), surgical face-lifts, abdominoplasty (tummy tuck), and liposuction, etc. referred to surgical procedures. In contrast, procedures such as chemical peels, filler, and botulinum toxin injections, laser skin resurfacing, vein removal, and laser hair removal are collectively referred to as non-surgical procedures. In recent years cosmetics surgeries have decreased while people have moved towards non-invasive cosmetic procedures. Objective: Knowledge, Attitude, and Practice of Cosmetic procedure among the population of Al-Majmaah, Saudi Arabia, 2019-2020. Methodology: This is an observational cross-sectional study targeted Al- Majma’ah population. Half of the participants were asked to complete an electronic questionnaire and the remaining completed a paper-based questionnaire. The questionnaire was divided into four parts: Socio-Demographic Data, Knowledge, Attitude, and Practice of cosmetic procedures. Data were analyzed by using SPSS v.25. In addition, Pearson Chi-square tests applied to determine associations between qualitative variables. Results: Most of the participants were aged between 18-25 years. The majority were female. All of them have heard about cosmetic procedures. Social media was the most common source of information. More than half of the participants recognized different types of cosmetic procedures. More than two-thirds of them believed low self-esteem affects decisions about cosmetic procedures. Only 146 reported undergoing cosmetic procedures, where most of them underwent liposuction and hair removal. Personal desire was the primary source of motivation.,Whereas self satisfaction was the commonest cause for not considering such procedures. 244 of the participants reported their relatives had undergone cosmetic procedures Conclusion: Most of the participants had poor to moderate levels of knowledge regarding Cosmetic procedures. Most of the participants had a positive attitude regarding such a procedure. The prevalence of cosmetic procedures is somewhat uncommon as about one-third of the participants underwent surgical and non-surgical procedures.